Multiple motivations for preposing in selected Philippine languages - Rosero, Michael Wilson (2021)
Access online through this link: https://journals.upd.edu.ph/index.php/archive/article/view/9156
Keywords: Language and languages; Cebuano language; Linguistics; Dialects